2015
DOI: 10.1016/j.otsr.2014.07.035
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of fibrin sealant in knee surgery: A meta-analysis

Abstract: Patients undergoing knee surgery would benefit from high-dose fibrin sealant with reduced transfusion rate and unit, hospital stay and complications, while they might benefit little from it in total blood loss. However, the effects of a low-dose of fibrin in knee surgery remain inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Therefore, we used changes in Hb levels after 24 to 48 hours as a tool to determine the effect of hemostasis. Several studies have reported that the use of FS in orthopedic knee surgery was effective in reducing vascular bleeding and the need for routine blood transfusion [10,11]. FS reduced the complications related to blood transfusions and decreased the costs related to the transfusions and acute postoperative bleeding control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we used changes in Hb levels after 24 to 48 hours as a tool to determine the effect of hemostasis. Several studies have reported that the use of FS in orthopedic knee surgery was effective in reducing vascular bleeding and the need for routine blood transfusion [10,11]. FS reduced the complications related to blood transfusions and decreased the costs related to the transfusions and acute postoperative bleeding control.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reporting that the use of FS in knee surgery was effective in reducing vascular bleeding and routine blood transfusions have been published [10,11]. However, thus far, no study on the hemostatic effect of FS on the donor-site morbidity of LD flaps has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Blood loss control and prevention strategies include the use of pneumatic tourniquets, hypotensive anesthesia, blood transfusions, and pharmacological agents; the latter, however, may be related to complications inherent to their use. 5 6…”
Section: Introductionmentioning
confidence: 99%
“…As estratégias de controle e de prevenção da perda sanguínea incluem o uso de torniquetes pneumáticos, anestesia hipotensiva, hemotransfusões e agentes farmacológicos, sendo que estes últimos podem se relacionar a complicações inerentes ao seu uso. 5 6…”
Section: Introductionunclassified
“…Some approaches to reduce the bleeding during orthopedic surgery, such as the use of fibrin sealant and/or tranexamic acid, have been used. 12,13 A clear understanding of the fibrinolytic dysregulation in these patients will help to develop adequate approaches to control bleeding. It has been reported that controlling the blood loss during surgery contributes to shorter hospital stay.…”
Section: Introductionmentioning
confidence: 99%